A national anti-doping education programme reduces doping susceptibility in British athletes - Hurst, P.; King, A.; Massey, K.; Kavussanu, M.; Ring, C. (Psychology of Sport and Exercise, 2023)
The World Anti-Doping Agency`s International Standard for Education instructs that national and international sport organisations evaluate their education programmes. We addressed this directive by examining the effectiveness of a national anti-doping programme. Athletes (N = 302, 41% female) completed measures of doping susceptibility, intention to use dietary supplements, Spirit of Sport and moral values, anti-doping knowledge and practice, and whistleblowing, prior-to and three-months after attending an anti-doping education programme. At three-month follow-up, athletes reported decreased doping susceptibility and intention to use dietary supplements coupled with increased importance of values, anti-doping knowledge, anti-doping practice and whistleblowing. Within-participant, moderated-mediation analyses revealed that programme-related changes in doping susceptibility were indirectly related to changes in intention to use dietary supplements, and, that this indirect relationship was moderated by moral values. These findings confirm the effectiveness of a national anti-doping education programme and highlight the contribution of dietary supplement use and personal values to changes in doping susceptibility.